(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The following new species of dryinids were described: Aphelopus hassani and papuensis from Papua (New Guinea); Anteon abdulnouri and phoenicium from Lebanon; Anteon georgense from South Africa; Anteon malaysianum and gauldi from Malaysia; Anteon viraktamathi from India; Anteon bribianum, subnigrum and walesense from Australia; Prioranteon prinslooi from South Africa; Bocchus watshami from Namibia; Dryinus dayi from Madagascar; Dryinus bruneianus and Richardsidryinus gauldi from Brunei; Mesodryinus noyesi from Madagascar; Mesodryinus eardleyi from South Africa; Pseudogonatopus ghanensis from Ghana; Gonatopus omanensis from Oman; Gonatopus abdulnouri from Lebanon; Gonatopus transvaalensis and grobbelaari from South Africa; Gonatopus viraktamathi, superbus and delhiensis from India; Gonatopus bouceki from India and China; Gonatopus cantonensis from China. The males of some species known only on the basis of female specimens were moreover described: Tridryinus ampuliciformis (Turner), Neodryinus diffusus Olmi and Pseudogonatopus similis (Brues).